Job satisfaction and motivation to teach: predicting intrinsic and extrinsic factors towards retaining career-switchers in the teaching profession - Omar, Muhd Khaizer; Self, Mary Jo; Cole, Ki Lynn Matlock; Mat Rashid, Abdullah; Mohd Puad, Mohd Hazwan (Global Academic Excellence, 2018)
The teaching career is undoubtedly one of the most challenging professions with regards to other related service-type occupations. Evidently, throughout the history of the teaching career, numerous cases related to mental and health problem, high dropout rate nationwide, and behavioral delinquency among teachers have been reported in this particular field. In general, career-switchers are individuals who transitioned from their previous occupation into the teaching service. Indeed, this specific group of individuals is interested into the teaching service due to the gap eventuated from the high attrition rate of teachers. Inevitably, the role of career-switchers, especially for former industrial-based practitioners, is significant in Career and Technical Education. In light of this matter, this research focused on determining teaching job satisfaction factors of career-switchers and predicting which job satisfaction factors are prominent to career-switchers’ retention plan. In this study, a descriptive and correlational analysis was utilized to ascertain the objective of the study: (a) to determine the teaching job satisfaction factors of career-switchers of career and technical education teachers and (b) to identify the job satisfaction factors that influence career-switchers’ retention plan. The sample of the study was derived from 2670 CareerTech registered teachers in the Midwestern state using purposive sampling technique. Then, the data was gathered using an online survey named Qualtrics, which filtered the number of career-switcher to 272. Additionally, a chi-square analysis was employed and the result indicated that the factors of marital status, the teaching position of career-switchers, and highest degree earned were found significance with retention plan. Also, the regression analysis revealed six job satisfaction factors which influenced career-switchers to remain in the teaching profession. Subsequently, these six factors were summarized into four major themes: salary, teaching supports, teaching preparation, and motivation. Based on the findings, it was implied that career-switchers take into consideration of both extrinsic and intrinsic variables when deciding whether to stay or leave the teaching profession. On the same note, future research related to comparative analysis of career-switchers within different demographic contexts is highly suggested.